2014
DOI: 10.1302/0301-620x.96b7.33005
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine is toxic to chondrocyte cell cultures

Abstract: Ketamine has been used in combination with a variety of other agents for intra-articular analgesia, with promising results. However, although it has been shown to be toxic to various types of cell, there is no available information on the effects of ketamine on chondrocytes. We conducted a prospective randomised controlled study to evaluate the effects of ketamine on cultured chondrocytes isolated from rat articular cartilage. The cultured cells were treated with 0.125 mM, 0.250 mM, 0.5 mM, 1 mM and 2 mM of ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…The ratio of Bax/Bcl-2 expression was determined because its ratio is significant for determining whether a cell underwent apoptosis. 29 The Bax/Bcl-2 ratio was increased dose dependently in BRL-3A cells with Co 2+ and Co-NPs treatment ( Fig. 5 ).…”
Section: Resultsmentioning
confidence: 86%
“…The ratio of Bax/Bcl-2 expression was determined because its ratio is significant for determining whether a cell underwent apoptosis. 29 The Bax/Bcl-2 ratio was increased dose dependently in BRL-3A cells with Co 2+ and Co-NPs treatment ( Fig. 5 ).…”
Section: Resultsmentioning
confidence: 86%
“…In the cultured normal SMCs used in the present study, ketamine, but not norketamine, induced a cytotoxic effect on cell growth (data not shown). Similarly, ketamine has been reported to exert toxicity in chondrocyte cell cultures and induce cytoskeleton interruption ( 39 , 40 ). Collectively, these results suggested that ketamine may dose-dependently damage the urinary bladder and affect SMC stability.…”
Section: Discussionmentioning
confidence: 98%
“…Félix showed that ketamine exposure in the developmental phase in Zebra fish results in bone and cartilage malformations [12]. Moreover, Ozturk highlighted that intra-articular ketamine should not be used to control joint pain since it induces apoptosis of chondrocytes in vitro in clinically relevant concentrations [13]. The authors showed that 0.25 mM concentration decreased cell viability, while 0.5 mM, 1 mM, and 2 mM concentrations were definitely toxic to chondrocyte cultures.…”
Section: Discussionmentioning
confidence: 99%